FUNGSI MANGROVE SEBAGAI BIOFILTER LIMBAH BUDIDAYA UDANG VANAME PADA TAMBAK INTENSIF SUPM NEGERI BONE - Suryo Wirawan Anton; Anton Anton; Dewi Virgiastuti Jarir; Fatmah Fatmah; Harlina Usman; Ilmiah Kuruseng (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2020)
This research was conducted in Juli-September 2019 in the Intensive Bone Pond SUPM Negeri Bone, Bone Regency. This study aims to: (1) Describe the condition of the study site for pond intercropping patterns; (2) Knowing the type and density of mangroves at the study site; (3) Assessing the role of mangroves as biofilter for the pollution of vaname shrimp pond cultivation. The method used in data collection is done by direct measurement to the field for water quality at the location of the pond, the type and density of mangroves determined by using transects. The results showed that the pond intercropping pattern used in the Bone State SUPM Pond was a model of an open trench pond. The type of mangrove that dominates the research location is Rhizopora mucronata and for vegetation density each station was different where in the tree category station 1 had a vegetation density of 0.48 ind / m², station II was 0.87 ind / m², station III was 1.06 ind / m². For the stake category 1 station has a vegetation density of 0.24 ind / m², station II is 0.08 ind / m², station III is 0.68 ind / m². For the seedling category station 1 has a vegetation density of 77 ind / m², station II is 32 ind / m², station III is 15 ind / m². Mangroves in the vicinity of SUPM Bone Bone can play a role as biofilter for the pollution of vaname shrimp aquaculture results with measurements of water quality before and after passing through mangroves decreased